Application Of Percentage Method And Group Discussion To Improve The Ability To Present Student Opinion In Learning Pancasila - Wawan Hariyadi (Journal Of Social Science (JoSS), 2024)
This study aims to improve students' ability to express opinions in Pancasila learning by applying the percentage method and group discussion. The research uses a descriptive qualitative approach with 49 students from the Guidance and Counseling Study Program as subjects. Data were collected through observation and documentation during the learning process. The results show that the percentage method and group discussion effectively enhance students' fluency, courage, and appropriateness in presenting opinions according to the discussed context. Other indicators, such as clarity and the sequence of ideas, also showed improvement. Supporting factors in implementing these methods include the role of lecturers, student motivation, and adequate facilities and infrastructure. In conclusion, the percentage and group discussion methods have improved students' ability to express opinions in Pancasila learning.